Progression of Fetal Brain Lesions in Tuberous Sclerosis Complex - Gelot, Antoinette Bernabe; Represa, Alfonso (Frontiers in Neuroscience, 2020)
Tuberous sclerosis (TSC) is a multisystem autosomal dominant genetic disorder due to loss of function of TSC1/TSC2 resulting in increased mTOR (mammalian target of rapamycin) signaling. In the brain, TSC is characterized by the formation of specific lesions that include subependymal and white matter nodules and cortical tubers. Cells that constitute TSC lesions are mainly Giant cells and dysmorphic neurons and astrocytes, but normal cells also populate the tubers. Although considered as a developmental disorder, the histopathological features of brain lesions have been described in only a limited number of fetal cases, providing little information on how these lesions develop. In this report we characterized the development of TSC lesions in 14 fetal brains ranging from 19 gestational weeks (GW) to term and 2 postnatal cases. The study focused on the telencephalon at the level of the caudothalamic notch. Our data indicate that subcortical lesions, forming within and at the vicinity of germinative zones, are the first alterations (already detected in 19GW brains), characterized by the presence of numerous dysmorphic astrocytes and Giant, balloon-like, cells. Our data show that cortical tuber formation is a long process that initiates with the presence of dysmorphic astrocytes (by 19–21GW), progress with the apparition of Giant cells (by 24GW) and mature with the appearance of dysmorphic neurons by the end of gestation (by 36GW). Furthermore, the typical tuberal aspect of cortical lesions is only reached when bundles of neurofilament positive extensions delineate the bottom of the cortical lesion (by 36GW). In addition, our study reveals the presence of Giant cells and dysmorphic neurons immunopositive for interneuron markers such as calbindin and parvalbumin, suggesting that TSC lesions would be mosaic lesions generated from different classes of progenitors.